Multidisciplinary Management of a Fractured Premolar: A Case Report with Followup - Madhavi R. Kondapuram Seshu; Christopher Leslie Gash (Case Reports in Dentistry)
The general dental practitioner must consider orthodontic extrusion of a tooth when a subgingival defect, such as, crown fracture occurs before prosthetic rehabilitation, especially in the aesthetic zone. Extrusion enables the root portion to be elevated which exposes sound tooth structure for placement of restorative margins. This case report describes the multidisciplinary management of a fractured upper first premolar in a general dental practice. The forced orthodontic eruption is achieved by an endodontic attachment and sectional fixed appliance with an offset placed in the wire. The ability to extrude premolars with this method is complicated by heavy occlusal forces, occlusal interferences, and short clinical crown length. The tooth was restored with a titanium post, composite core, and porcelain fused to metal crown. The entire course of treatment was carried out under National Health Scheme, UK and as a part of vocational training. The 21 months followup showed no change in occlusal contacts or gingival level.